2012
DOI: 10.1093/brain/aws128
|View full text |Cite
|
Sign up to set email alerts
|

Social cognitive deficits and their neural correlates in progressive supranuclear palsy

Abstract: Although progressive supranuclear palsy is defined by its akinetic rigidity, vertical supranuclear gaze palsy and falls, cognitive impairments are an important determinant of patients’ and carers’ quality of life. Here, we investigate whether there is a broad deficit of modality-independent social cognition in progressive supranuclear palsy and explore the neural correlates for these. We recruited 23 patients with progressive supranuclear palsy (using clinical diagnostic criteria, nine with subsequent patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
90
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 111 publications
(98 citation statements)
references
References 138 publications
(254 reference statements)
7
90
1
Order By: Relevance
“…Finally, greater cerebellar atrophy in patients with PSP correlated with lower Frontal Assessment Battery scores, greater postural instability (lobules I–IV) and disease duration (lobules I–IV, VIIIb),36 decreased phonological verbal and letter fluency (left lobule VI, right I–IV)36 37 and impaired emotion recognition and theory of mind (right Crus II) 38…”
Section: Resultsmentioning
confidence: 92%
“…Finally, greater cerebellar atrophy in patients with PSP correlated with lower Frontal Assessment Battery scores, greater postural instability (lobules I–IV) and disease duration (lobules I–IV, VIIIb),36 decreased phonological verbal and letter fluency (left lobule VI, right I–IV)36 37 and impaired emotion recognition and theory of mind (right Crus II) 38…”
Section: Resultsmentioning
confidence: 92%
“…Multiple studies have demonstrated impaired social cognition in AD, including deficits in moral judgments and decision making (Torralva et al, 2000) and deficient reasoning regarding psychological versus physical causation (Verdon et al, 2007). Additionally, other patient populations including PSP, VaD and PD have been reported to have social cognitive changes to varying degrees (Allain et al, 2011; Bodden et al, 2010; Ghosh et al, 2012; Kawamura et al, 2007; Roca et al, 2010; Yu et al, 2012). However, a recent study directly comparing dementia groups revealed more severe social cognitive deficits in bvFTD as compared to non-FTD groups.…”
Section: Social Cognition In the Diagnosis Of Ftd Syndromesmentioning
confidence: 99%
“…Many studies found a diminished gray matter density (GMD) in the left and right insulae (Brenneis et al, 2004; Padovani et al, 2006; Ghosh et al, 2012). Several papers reported a reduced GMD in the thalamus (Cordato et al, 2005; Boxer et al, 2006; Padovani et al, 2006; Shi et al, 2013), but other papers did not find GMD changes here (Brenneis et al, 2004; Ghosh et al, 2012). Volumetric analysis of structural MRI showed a significantly smaller putamen in PSP patients in comparison to healthy controls (Messina et al, 2011).…”
Section: Introductionmentioning
confidence: 99%